1995
DOI: 10.1128/aac.39.4.921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testing method on apparent activities of antiviral disinfectants and antiseptics

Abstract: This study was designed to evaluate the independent effects of various test methods on the activities of antiviral chemical germicides. The activities of germicides against MS2 and 6 bacteriophages in a new porcine tissue carrier model were compared to those obtained by four other methods (suspension, glass carrier, tile carrier, and fingerpad tissue carrier tests). After a 1-min contact followed by neutralization (and elution off the carriers), the residual virus in the treated samples was quantified and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…Carrier tests, which are commonly performed by dipping or spiking the viral challenge onto the substrate, do not account for the physical characteristics of aerosols, such as particle size, composition, velocity, desiccation, and subsequent substrate penetration (8,21,30). It has been shown previously that the testing method has an effect on the activities of disinfectants (9,24,38). Woolwine and Gerberding showed that inactivation of FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrier tests, which are commonly performed by dipping or spiking the viral challenge onto the substrate, do not account for the physical characteristics of aerosols, such as particle size, composition, velocity, desiccation, and subsequent substrate penetration (8,21,30). It has been shown previously that the testing method has an effect on the activities of disinfectants (9,24,38). Woolwine and Gerberding showed that inactivation of FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The virus suspension (10 11 PFU/ml) was stored at 4°C in 50-ml conical tubes (Falcon, Becton Dickinson) for use in experiments. MS2 was selected for the study based on its moderate resistance to disinfectants, survivability, ease of preparation and assay, and nonpathogenicity (18,38).…”
Section: Bartsmentioning
confidence: 99%
“…MS2 has been used in place of pathogens in a large number of studies: for examining the survival of viruses on produce (1,11), developing systems and methods to remove viruses from water and surfaces (5, 9, 10, 12, 13, 17-20, 23-25, 29, 30, 32-34, 42), and investigating the fate of pathogens in groundwater (2,14,15,26,31,(36)(37)(38)(39). It has also been used in the testing and development of systems for the detection of biological warfare agents (3,8,22,35,40,41).…”
mentioning
confidence: 99%
“…For example, determination of the minimum inhibitory concentration (MIC) of such formulations against bacteria has no direct bearing on the "killing effect" expected of such products in the field. Conditions in suspension and in vitro 192 or ex vivo 193 testing do not reflect those on human skin. Even simulated-use tests with subjects are considered by some as "too controlled", prompting testing under in praxi or field conditions.…”
Section: Methods To Evaluate the Antimicrobial Efficacy Of Handrub Anmentioning
confidence: 99%
“…297 Other enveloped viruses that are somewhat less susceptible, but are killed by 60-70% alcohol, include hepatitis B virus (HBV) and probably hepatitis C virus. 298 In a porcine tissue carrier model used to study antiseptic activity, 70% ethanol and 70% isopropanol were found to reduce titres of an enveloped bacteriophage more effectively than an antimicrobial soap containing 4% CHG. 192 Numerous studies have documented the in vivo antimicrobial activity of alcohols. Early quantitative studies of the effects of antiseptic handrubs established that alcohols effectively reduce bacterial counts on hands.…”
Section: Alcoholsmentioning
confidence: 99%